Restaurant Understanding Training For Students At Al-Jabar Private Vocational School Batam - Pratama, Tito; Dailami, Dailami; Thandzir, Moh.; Sukmamedian, Haufi; Ulum Lubis, Taufik Bachrul (PUSLITABMAS-Politeknik Pariwisata Batamc, 2025)
Restaurant Understanding Training is an educational activity designed to equip students with basic knowledge and skills regarding the world of work in the restaurant sector. The training material includes an introduction to types of restaurants, service standards, work procedures, cleanliness management, and professional ethics in serving customers. Through this training, participants are expected to be able to understand the workflow in the restaurant industry and increase their readiness to face the world of work and entrepreneurship in the culinary sector